Renaissance Epitaph as Medium of „Confessional Identity“ in the Context of Town Chrudim before 1620. Monument of Thomas Lvík of Domažlice (†1616) and Salomena Francová of Liblice (†1619) as historically-anthropological source (Theatrum historiae, 2008)
The study deals with a unique epitaph monument of Chrudim couple of Thomas Lvík of Domažlice and his wife Salomena Francová of Liblic (after 1619). The central scene of the epitaph represents very rare iconography – Allegorical Crucifixion. We can find similar allegorical scenes especially at Silesian protestant epitaphs around 1600. The paper tries to take advantage of this painted epitaph to use it as specific historical source comparable with traditional written documents. Because we suffer from lack of personal and individual references in these traditional documents it seems to be useful to look round for other sources. We realize this deficiency especially in the context of sepulchral culture when we try to find out something about religious mentality of early modern people. The specific iconography of the Chrudim epitaph provides us very unique opportunity for observing religious ideas of Non-Catholic in case of town of Chrudim. Comparing with similar epitaph it seems relevant to consider this Lvík's monument as reflection of typically protestant hopeful eschatological teaching. There is no problem with the fact that it was „Catholic“ etching that served as graphic pattern for this epitaph. More important is „using“ of such iconographical theme in concrete non-Catholic environment of Chrudim. The aim of the article is to demonstrate that even „image“ can serve as competent historical source, but only in case we are capable to analyze and interpret it rightly, that means to propound correct questions.